2020
DOI: 10.1007/s41742-020-00280-3
|View full text |Cite
|
Sign up to set email alerts
|

Coprecipitation Synthesis of Fe-Doped TiO2 from Various Commercial TiO2 for Photocatalytic Reaction

Abstract: The current work reports the synthesis of Fe-doped TiO 2 nanoparticles by simple coprecipitation method and compares their photocatalytic efficiency to three different commercially available TiO 2 (i.e., Sachtopore, Hombikat UV100 and Fluka) using methyl orange (MO) under UV light irradiation. X-ray diffraction (XRD), diffuse reflectance spectroscopy (DRS) and transmission electron microscopy (TEM) were used to characterize these synthesized Fe-doped TiO 2 nanoparticles. In fact, the DRS results revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Microwave irradiation is a highly appealing method, which has been employed in several studies for its simplicity, homogeneous and fast heating, cost-effectiveness, selective heating, and facility of reaction scale-up [ 13 , 48 , 49 , 50 , 51 , 52 ]. Although several studies on the synthesis of Fe-doped TiO 2 are reported in the literature, most of them employed methods that involve a considerable amount of time and a calcination step, which typically requires the use of high temperatures [ 53 , 54 , 55 , 56 , 57 ]. Regarding the microwave irradiation method, few studies have focused on a fast Fe-TiO 2 microwave synthesis without the need to calcinate the samples; the approach developed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave irradiation is a highly appealing method, which has been employed in several studies for its simplicity, homogeneous and fast heating, cost-effectiveness, selective heating, and facility of reaction scale-up [ 13 , 48 , 49 , 50 , 51 , 52 ]. Although several studies on the synthesis of Fe-doped TiO 2 are reported in the literature, most of them employed methods that involve a considerable amount of time and a calcination step, which typically requires the use of high temperatures [ 53 , 54 , 55 , 56 , 57 ]. Regarding the microwave irradiation method, few studies have focused on a fast Fe-TiO 2 microwave synthesis without the need to calcinate the samples; the approach developed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Their product exhibits a remarkably high photocatalytic capacity to evolve hydrogen, to an extent of 850 mmol/5 mg within 40 min. Next to these examples, a large number of other publications have published on the doping of TiO 2 nanoparticles [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%